Pemanfaatan Bakteri Bacillus sp Pada Sektor Pertanian - Mulyono, Mulyono; Candra, Ifan Aulia (Universitas Medan Area, 2025)
Modern agriculture faces serious challenges due to its high dependence on chemical fertilizers, which in the long run leads to soil degradation, environmental pollution, and a decrease in the diversity of soil microorganisms. One of the innovative approaches that is now widely developed is the use of soil microorganisms as biological agents, especially Bacillus sp. This study aims to examine the role of Bacillus sp. in improving soil fertility and plant productivity in a sustainable manner through literature studies. A total of 25 relevant scientific articles published in 2015–2024 were thematically analyzed based on aspects of phosphate dissolution, enzyme production, biocontrol capabilities, and increased plant growth. The results of the study show that Bacillus sp. It has the ability to increase nutrient availability, inhibit plant pathogens, improve soil structure, and stimulate root growth through the production of phytohormones. However, its effectiveness is greatly influenced by the type of plant and the condition of the agroecosystem. With proper management, Bacillus sp. can be a leading alternative to reduce the use of chemical fertilizers and encourage sustainable agriculture that is environmentally friendly and efficient.